Catalytic and DNA-binding properties of the human Ogg1 DNA N-glycosylase/AP lyase: biochemical exploration of H270, Q315 and F319, three amino acids of the 8-oxoguanine-binding pocket - van der Kemp, Patricia Auffret (Oxford University Press, 2004)
The human Ogg1 protein (hOgg1) is an antimutator DNA glycosylase/AP lyase that catalyzes the excision of 8-oxo-7,8-dihydroguanine (8-oxoG) and the incision of apurinic and apyrimidinic (AP) sites in DNA. In this study, we have investigated the functional role of H270, Q315 and F319, three amino acids that are located in the 8-oxoG-binding pocket of hOgg1. Wild-type and mutant hOgg1 proteins (H270A, H270R, H270L, Q315A and F319A) were purified to apparent homogeneity. The catalytic activities and the DNA-binding properties of the various hOgg1 mutants were compared to those of the wild-type. The results show that hOgg1 mutated at H270 (H270A and H270L) or F319 (F319A) exhibits greatly reduced (50- to 1000-fold) DNA glycosylase activity, whereas the AP lyase activity is only moderately affected (<4-fold). The affinity of the hOgg1 mutants (H270A, H270L and F319A) for 8-oxoG.C-containing DNA is also greatly reduced (>30-fold), whereas their affinity for THF.C-containing DNA is only moderately reduced (<7-fold). The results also show that hOgg1 mutated at Q315 (Q315A) exhibits catalytic and DNA-binding properties similar to those of the wild-type. Therefore, H270 and F319 are essential to form the functional 8-oxoG-binding pocket, whereas Q315 is less crucial. In contrast, H270, Q315 and F319 are not required for efficient binding of THF.C and cleavage of AP sites. Finally, hOgg1 mutant proteins with a substitution of H270A or F319A are members of a new type of hOgg1 that is deficient in DNA glycosylase but proficient in AP lyase.